Psychology for living : adjustment, growth and behavior today - Kirsh, Steven J. (Pearson, 2015)
The eleventh edition of Psychology for Living: Adjustment, Growth, and Behavior Today is designed for students interested in applying psychological insights and principles to their own lives. The text helps readers achieve a better understanding of themselves and others.